Attachment promoting compounds significantly enhance cell proliferation and purity of bovine satellite cells grown on microcarriers in the absence of serum - Bodiou, Vincent; Kumar, Anitha Ajith; Massarelli, Edoardo; van Haaften, Tessa; Post, Mark J.; Moutsatsou, Panagiota (Frontiers in Bioengineering and Biotechnology, 2024)
To bring cultivated beef to the market, a scalable system that can support growth of bovine satellite cells (bSCs) in a serum-free and preferably also animal-free medium is of utmost importance. The use of microcarriers (MCs) is, at the moment, one of the most promising technologies for scaling up. MCs offer a large surface to volume ratio, they can be used in scalable stirred tank bioreactors, where the culture conditions can be tightly controlled to meet the cells' requirements (temperature, pH, dissolved oxygen). The inherent capacity of the cells to migrate from one MC to another, also known as bead-to-bead transfer, facilitates a scale-up strategy involving MCs. Previous studies have shown growth of bSCs on three commercially available MCs in serum containing media. Unfortunately there is currently no information available regarding their growth on MCs in serum-free conditions. In this study, we aimed to find suitable serum-free media, MCs and attachment promoting compounds (APCs) supporting the growth of bSCs. Initially, six commercial MCs and three serum-free media were evaluated.The effects of three APCs were compared (vitronectin, laminin and fibronectin). Subsequently, the effects of different concentrations and modes of addition of the best performing APC were investigated. Our results showed that Cytodex 1, Synthemax II and CellBIND supported bSCs' growth in all serum-free media. Overall, better growth was observed with Cytodex 1 in serumfree proliferation media. We showed that the use of laminin or vitronectin with Cytodex 1 can significantly improve cell growth and purity. Laminin also allowed attachment and growth of bSCs on Plastic MCs which had been previously unsuccessful without APCs. Finally, we optimized the use of vitronectin from a sustainability and process perspective, and showed that it can be used solely as a coating for Cytodex 1 (16-100 ng/cm2 ) MCs, instead of as a medium supplement, enhancing cell attachment and proliferation.